EFFECT OF USING E-BOOK BALANCING ECOSYSTEM BASED ON CHARACTER EDUCATION (RELIGIOUS VALUES) ON STUDENT LEARNING ACHIEVEMENT - CANDRA DEWI (Universitas Muhammadiyah Ponorogo, 2021)
This study aims to determine the effect of using e-book balancing ecosystem based on character education (religious values) on student achievement. This study used experimental research methods and the design used was a quasi-experimental design using post test Only Control Design research. The sample to be used is 40 students of fifth grade Elementary School which are divided into two classes, namely the experimental class and the control class. The data collection techniques used were tests, documentation and observation. After conducting the research, it can be analyzed that the learning achievement scores of the two classes are higher in the experimental class than the control class. After testing the hypothesis (T-test), the results obtained are Tcount = 3,315 Ttable 1,686 then H0 is rejected and H1 is accepted. Thus, it can be concluded that the result of this study is that there is an effect of the use of the e-book on the balance of the ecosystem based on character education (religious values) on the learning achievement of elementary school students.